Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jeb.13620
|View full text |Cite
|
Sign up to set email alerts
|

Biased predation could promote convergence yet maintain diversity within Müllerian mimicry rings of Oreina leaf beetles

Abstract: Aposematic signals that warn predators about prey defences have long occupied biologists' attention as a prime example of adaptation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Models exploring the foraging behaviour of predators nevertheless suggest that their discrimination capacities depend on a more complex interplay between the profitability and colour pattern variation found in prey communities (Getty 1985). Several cognitive biases in predators, not modelled in our study, might also favour the invasion of more conspicuous warning colour patterns in defended species: biased predation (Kikuchi et al 2020), innate memorability, direct deterrence, diet conservatism (Marples et al 2005) or neophobia (Marples andKelly 1999, Aubier andSherratt 2015) have indeed been shown to promote the emergence of new warning patterns. Our study thus calls for attention to the effect of ecological interactions with other defended species, edible alternative prey, and of the diversity of colour pattern in sympatric species on the evolution of aposematism in defended species.…”
Section: Evolution Of More Conspicuous Colour Patterns Can Be Promote...mentioning
confidence: 69%
See 1 more Smart Citation
“…Models exploring the foraging behaviour of predators nevertheless suggest that their discrimination capacities depend on a more complex interplay between the profitability and colour pattern variation found in prey communities (Getty 1985). Several cognitive biases in predators, not modelled in our study, might also favour the invasion of more conspicuous warning colour patterns in defended species: biased predation (Kikuchi et al 2020), innate memorability, direct deterrence, diet conservatism (Marples et al 2005) or neophobia (Marples andKelly 1999, Aubier andSherratt 2015) have indeed been shown to promote the emergence of new warning patterns. Our study thus calls for attention to the effect of ecological interactions with other defended species, edible alternative prey, and of the diversity of colour pattern in sympatric species on the evolution of aposematism in defended species.…”
Section: Evolution Of More Conspicuous Colour Patterns Can Be Promote...mentioning
confidence: 69%
“…We assume that variation in the level of conspicuousness between the ancestral and derived phenotypes can modify the level of similarity perceived by predators, thereby modulating predator generalization (Kikuchi andPfennig 2013, Motyka et al 2020). Mutations can thus generate derived colour patterns that are perceived as slightly different from the ancestral phenotype by the predators (i.e.…”
Section: Imperfect Mimicrymentioning
confidence: 99%
“…However, additional reasons may explain the observed pattern, and the biological significance of elytra colouration as revealed in other species of beetles should be considered [8][9][10][11]. Intraspecific variability of the elytra colour in beetles can be associated with (i) the trophic pressure of predators (for example, birds or mammals may be more likely to prey upon some colour morphs) [12], (ii) the better reflective ability of white colouration in hot climates (prevention of excessive body heating in individuals with larger body sizes and, accordingly, slower heat transfer to the surrounding space) [13] and the better wettability [14], (iii) different humidity levels at the local population scale [15,16], (iv) the domination of different colour morphs of beetles in different types of plant communities or landscapes [17], (v) a different set of food for the larvae, as a result of which different digestive enzymes are expressed, some of which can be linked to the genes for wing colouring [17], or (vi) direct mechanical collection of beetles with white elytra (as we pointed out at above). The anthropogenic impact on beetles can be both direct (mechanical extermination of a given morphological form) and indirect (for example, through changes in the fauna of parasites of larvae, pupae, or adults, destruction of any food plants, pollution of the environment by insecticides, fungicides, herbicides, heavy metals, or persistent organic pollutants) [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…The species of this largely Alpine, Palearctic genus [ 14 ] are colorful and chemically defended [ 8 ]. Within the Alps, at least six species of Oreina display a basal color of either blue or green and they may coexist in patchily distributed locations [ 12 , 15 , 16 ]. Laboratory assays of predatory behavior suggested that bird predators learned to associate color with chemical defenses, and that learned avoidance of the green morph of one species protected green morphs of another species, configuring a classic case of müllerian mimicry [ 16 ].…”
Section: Introductionmentioning
confidence: 99%